Adapting the Research Development and Innovation (RD & I) Value Chain in Psychology to Educational Psychology Area - de la Fuente, Jesús; Kauffman, Douglas; Díaz-Orueta, Unai; Kauffman, Yashu (Frontiers in Psychology, 2018)
Educational Psychology, as an area of Psychology that specializes in formative processes, faces several important challenges in the information and knowledge society of this 21st century. One of these challenges is to facilitate a paradigm shift from a nearly exclusive focus on social science to the scientific-technological approach of a discipline that produces innovation and meaningful transfer of science and technology. The Research, Development, and Innovation (R D & I) value chain means pursuing these three endeavors in both the academic and professional lines of Educational Psychology. It is a strategy of innovation that leads us to integrate academic or research activity (R), research-related or professional scientific-technological development of innovation (D) and transfer and entrepreneurship activity (I). Generating innovation and transfer, applicable to educational contexts, can be an important stimulus of activity for new practicing psychologists in Educational Psychology. The R D & I value chain can become an academic, research-related or professional advantage in different activities, since it pertains to the processes, products and services found in the sphere of Educational Psychology. Several examples of how the R D & I chain can help improve psychoeducational activities are presented. First, we analyze competitive improvements that the R D & I chain can offer in competitive bids. Second, we give examples of the R D & I chain in the development of new processes, products and services in Projects of Innovation and Entrepreneurship in Educational Psychology, specifically illustrating the chain in each case. In order for this conception to take shape, a new cross-functional area must be created in professional and educational organizations. Specifically, this means creating an R D & I Department, or some area that branches across the other functions. The mission of this cross-functional unit is the actual implementation of the R D & I chain in the educational organization, as well as an incentive for innovative activities: use of ICT applications, organizational improvement, improved assessment, analysis of information produced by the organization itself, cost-benefit analysis, strategic decision-making processes, and so on.